Pengaruh Work-Study Conflict terhadap Turnover Intention pada Karyawan yang Berkuliah - Bramasta Dimas Hartato; Sartika, Dewi; Permana, Rizka Hadian (UNISBA Press, 2024)
Abstract. Work-study conflict is defined as a condition in which an individual feels a conflict in his professional obligations at work and in his educational obligations in college (Markell & Fronel, 1998)3. Turnover Intention is the tendency or intention of an employee to voluntarily resign or move from one place of work to another according to his own choice (Moblely et al, 1978)6. This study aims to determine whether there is an effect of work-study conflict on turnover intention in employees who study in Bandung City. Researchers collected data using the work-study conflict scale from Markel and Frone (1998)3 which was adapted by Aini (2022)8 and the turnover intention scale from Mobley et.al (1978)6 which was adapted by Farisan (2022)9. In the statistical test process, this study uses simple regression analysis and the results of this study show the influence between work-study conflict on turnover intention with a value of R = 0.623 or it can be said that the work-study conflict variable has a contribution of 62.3% to turnover intention. Abstrak. Work-study conflict didefinisikan sebagai sulatul kondisi di mana selselorang melrasakan konflik dalam kelwajiban profelsionalnya dalam pekerjaan dan dalam kelwajiban pelndidikannya di perkuliahan (Markell & Fronel, 1998)3. Tulrnovelr Intelntion adalah kelcelndelrulngan ataul niat selorang karyawan ulntulk selcara sulkarella melngulndulrkan diri ataul belrpindah dari satul telmpat kelrja kel telmpat kelrja lain selsulai delngan pilihannya selndiri (Moblely elt al, 19786). Penelitian ini bertujuan untuk mengetahui apakah ada pengaruh work-study conflict terhadap turnover intention pada karyawan yang berkuliah di Kota Bandung. Peneliti melakukan pengambilan data menggunakan skala work-study conflict dari Markel dan Frone (1998)3 yang diadaptasi oleh Aini (2022)8 dan skala turnover intention dari mobley et. al (1978)6 yang di adaptasi oleh Farisan (2022)9. Dalam proses uji statistik penelitian ini menggunakan analisis regresi sederhana dan hasil dari penelitian ini menunjukkan pengaruh antara work-study conflict terhadap turnover intention dengan nilai R= 0,623 atau dapat dikatakan variabel work-study conflict memiliki kontribusi sebesar 62,3% terhadap turnover intention.